KOMPOSISI SERANGGA YANG BERASOSIASI DENGAN POHON MASOY (Cryptocarya massoy) DI AMBAIDIRU YAPEN WAROPEN PAPUA - , Srihartati Harto, S.Hut, Dr. Nugroho Susetya Putra, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Masoy as a endemic plant in Papua has potency for human life, such as in agriculture, for botanical insecticides. Data and information on relationship between masoy and insects are very limited. This study aims to determine the composition of insects associated with trees masoy (Cryptocarya massoy) in Papua Ambaidiru. The method used is survey method. Ambaidiru defined as the study site, with gardens and forest ecosystems to determine the secondary as an area of observation, observation trees intentionally is determined as much as 3 trees. Observations were also performed on the floor around the tree and vegetation in both areas. The collection of insect sticky traps, pitfall traps and sweep nets. The data obtained were analyzed using descriptive statistics, to obtain the number and percentage of the amount needed. The analysis showed that, masoy association between trees and insects in the garden and forest ecosystems differently, in the garden area is more varied than the forest. In the area of the garden found 769 individuals who are grouped into 17 orders, 95 family and 33 genera